2022
DOI: 10.3390/jcm11216446
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of C-Reactive Protein Apheresis in Acute Myocardial Infarction—Results from a Supplementary Data Analysis of the Exploratory C-Reactive Protein in Acute Myocardial Infarction-1 Study

Abstract: In the multicenter, non-randomized, exploratory C-reactive protein (CRP) Apheresis in Myocardial Infarction (CAMI-1) study, CRP apheresis after ST-Elevation Myocardial Infarction (STEMI) significantly decreased blood CRP concentrations in humans. Cardiac damage was assessed by Cardiac Magnetic Resonance (CMR1) 3–9 d after onset of STEMI symptoms and quantified by myocardial infarct size (IS; %), left ventricular ejection fraction (LVEF; %), circumferential strain (CS) and longitudinal strain (LS). Compared wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In this protocol, patients are subjected to a 4-6 h extracorporeal circuit and blood plasma is applied to phosphocholine-linked resin. A case report and studies on small cohorts of patients with ST elevation myocardial infarction (STEMI) demonstrated efficient lowering of plasma CRP levels ( 47 , 102 , 114 , 115 ). However, results from the multi-center pilot CAMI-1 (CRP Apheresis in Acute Myocardial Infarction-1) study were inconclusive in regard with correlation of reduced CRP levels with myocardial infarct size ( 47 ) because the study was not randomized.…”
Section: Crp As a Target For Therapymentioning
confidence: 99%
“…In this protocol, patients are subjected to a 4-6 h extracorporeal circuit and blood plasma is applied to phosphocholine-linked resin. A case report and studies on small cohorts of patients with ST elevation myocardial infarction (STEMI) demonstrated efficient lowering of plasma CRP levels ( 47 , 102 , 114 , 115 ). However, results from the multi-center pilot CAMI-1 (CRP Apheresis in Acute Myocardial Infarction-1) study were inconclusive in regard with correlation of reduced CRP levels with myocardial infarct size ( 47 ) because the study was not randomized.…”
Section: Crp As a Target For Therapymentioning
confidence: 99%
“…It was also shown that patients with high CRP synthesis rates after AMI benefit most from CRP-targeting therapy and that the reduction of myocardial damage, assessed by infarct size and LVEF in cardiac magnetic resonance imaging (CMR), was sustained after scar formation is considered complete [ 89 ].…”
Section: Crp Causes the Disposal Of Ischemic And Hypoxic Cellsmentioning
confidence: 99%